Violence and creation: The recovery of the body in the work of Elaine Scarry. Issue 4 (December 2016) - Brown, Steven
Abstract Elaine Scarry's bookThe Body in Pain justly deserves its place as one the pivotal works that opened up the field of 'body studies'. The text needs to be evaluated in the retrospective terms of the field it established, and also with respect to the changing status of both 'torture' and 'war' in contemporary state politics. Scarry's analysis of the relationship between making and unmaking, tools and weapons, under-estimates the reversibility and the situated relational character of these processes and artefacts. The changing nature of modern conflict, and the rising concern with global terrorism rather than 'conventional' and 'nuclear' war, makes the 'referential instability' of the body difficult to recuperate in post-conflict discourse. At the same, the normalization of the logic of torture in the contemporary governance of the bodies of the most vulnerable in society makes Scarry's analysis all the more prescient.